Cage Loads of Wind Turbine Blade Bearing. Issue 5 (September 2020) - Buescher, M; Leupold, S; Schelenz, R; Jacobs, G
Abstract: Slewing bearings of wind turbine blades pitch system allow the required oscillation while transferring complex dynamical loads from the rotor blades towards the hub. Most common for this application are double rowed four-point contact ball bearings consisting of two rings and two rolling element sets either equipped with a ring cage or with spacers. By equally distributing the rolling elements along the circumference, the bearing cage balances the loads along the raceways and thereby actively prevents damage mechanisms. However, cage stress analyses imply further optimization potentials leading to higher load capacities and the prediction of cage damaging mechanisms via dynamic simulations. This contribution presents a simulation procedure that calculates rolling element dynamics at the presence of a ring cage by taking the perpendicular movement of the contact ellipses due to the elastic deformations of the bearing rings into account. The procedure is carried out exemplary by the load spectra of a 3 MW reference wind turbine and the actual geometry of a 2.4m diameter bearing.